2015
DOI: 10.1628/001522115x14206439673251
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Profit Shifting with Tax-sensitive Capital Stocks

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This argument is supported with evidence found by Bartoloni (2013) and Loretz and Mokkas (2015). Before the results is discussed it is important to note our selection of control variables is in line with Frank and Goyal (2009) who identified that capital structure determinants must include among others firm size and inflation.…”
Section: Effect On Capital Structuresupporting
confidence: 77%
“…This argument is supported with evidence found by Bartoloni (2013) and Loretz and Mokkas (2015). Before the results is discussed it is important to note our selection of control variables is in line with Frank and Goyal (2009) who identified that capital structure determinants must include among others firm size and inflation.…”
Section: Effect On Capital Structuresupporting
confidence: 77%
“…Dharmapala (2014) reviews the literature on how the reported income changes with respect to tax rates differs across countries, represented by Hines and Rice (1994), Huizinga and Laeven (2008) and Dharmapala and Riedel (2013). Grubert and Mutti (1991), as well as Clausing (2003Clausing ( , 2016, provide evidence for the US; Huizinga and Laeven (2008), Weichenrieder (2009) and Loretz and Mokkas (2015) present more recent evidence for European multinationals. According to the consensus of the recent literature by Heckemeyer and Overesch (2013), who followed the earlier meta-analysis by de Mooij and Ederveen (2008), a semi-elasticity of reported income with respect to the tax rate differential across countries amounts to 0.8.…”
mentioning
confidence: 99%
“…See Grubert and Mutti (1991) for early evidence for the US; Huizinga and Laeven (2008), Weichenrieder (2009) and Loretz and Mokkas (2011) for more recent evidence for European multinationals.…”
mentioning
confidence: 99%